Spectacles of Shame: Ryan Murphy as Curator of Queer Cultural Memory - Stepić, Nikola N. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
In the anthology Queer Shame, edited by David M. Halperin and Valerie Traub, “the personal and the social shame attached to eroticism” is taken to task in relation to the larger contemporary discourse surrounding gay pride (understood in terms of activism and cultural production), while being seen as a defining characteristic of queer history, culture and identity. Shame, as theorized by Eve Kosofsky Sedgwick, Halperin and others, is predicated on a larger issue of queer people’s access to discursive power, which Sedgwick herself had theorized in The Epistemology of the Closet. Such a conceptualizing of queer culture and queer politics begs the interrogation of how queer shame is contained and negotiated in contemporary popular culture. One of the most successful auteurs working in film and television today, Ryan Murphy’s opus is marked by a constant dialogue with queer cultural artifacts. The excitement that his productions generate is typically predicated on his use of queer cultural objects, especially as they are rearticulated for mainstream audiences. This paper investigates the inherent shame of queer memory as embodied in Murphy’s show American Horror Story through reference and negotiation of queer icons, filmic traditions and on-screen bodies. Utilizing queer and film theory as its framework, this paper treats Murphy’s queer vernacular as the uncanny that destabilizes conventions of both the horror genre and mainstream television, in turn legitimizing and exploiting “shameful” queer categories such as trauma, excess, diva worship and camp through the language of popular television and the bodies that populate it. Finally, this essay evaluates the productive power of Murphy’s repository of “disgraceful” bodily images—allegorical and literal—in furthering a critical remediation of the vernacular of queer shame.